Peran Intellectual Capital Terhadap Organizational Value - Dodi Siswanto (KarismaPro, 2019)
The discussion related to Intellectual Capital becomes a very interesting matter for organizations, this is because intellectual capital is an invisible asset that can have an extraordinary impact, can provide added value to the company so as to increase organizational competitiveness. Therefore, business owners (MSMEs) need to be aware of this. The purpose of this research is to examine how strategies to strengthen intellectual capital in increasing the organizational value of MSMEs. The dimensions studied in this study are Human Capital, Capital Structure, Customer Capital, and Social Capital. This type of research uses qualitative methods with a literature study approach. This human capital formation can be done through employee self-development by providing education and training. Learning about culture, infrastructure, and the right incentives to generate and disseminate knowledge are ways to strengthen the Capital Structure. Providing excellent service is an effort to retain customers. Bonding Social Capital, Bridging Social Capital, Linking Social Capital are social capital that can provide a conceptual understanding that social capital that is formed can create different results.Keywords: Intellectual capital, organizational values.